Hard X-ray nanoprobe at beamline P06 at PETRA III - Schroer, Christian G.; Boye, Pit; Feldkamp, Jan M.; Patommel, Jens; Samberg, Dirk; Schropp, Andreas; Schwab, Andreas; Stephan, Sandra; Falkenberg, Gerald; Wellenreuther, Gerd; Reimers, Nadja (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2010)
We describe the hard X-ray scanning microscope planned for the new synchrotron radiation source PETRA III at DESY in Hamburg, Germany. It is based on nanofocusing refractive X-ray lenses and is designed for two-dimensional mapping and scanning tomography. It supports X-ray fluorescence and (coherent) diffraction contrast, yielding elemental and structural information from inside the sample. Spatial resolutions down to well below 50 nm are aimed for in direct space. A further increase in spatial resolution is expected by applying ptychographic scanning schemes. The optical scheme with a two-stage focusing optic is described.